Virtual reality for the rehabilitation and prevention of intimate partner violence – From brain to behavior: A narrative review - Johnston, Tania; Seinfeld, Sofia; Gonzalez-Liencres, Cristina; Barnes, Nicolas; Slater, Mel; Sanchez-Vives, Maria V. (Frontiers in Psychology, 2023)
Rehabilitation and prevention strategies to reduce intimate partner violence (IPV) have limited effectiveness in terms of improving key risk factors and reducing occurrence. Accumulated experimental evidence demonstrates that virtual embodiment, which results in the illusion of owning a virtual body, has a large impact on people’s emotional, cognitive, and behavioral responses. This narrative review discusses work that has investigated how embodied perspective - taking in virtual reality has been used as a tool to reduce bias, to enhance recognition of the emotional state of another, and to reduce violent behaviors, in particular in the realm of IPV. Some of the potential neurological mechanisms behind these affective and behavioral changes are also discussed. The process of rehabilitation and prevention is complex and not always effective, but the integration of neuroscience-inspired and validated state-of-the-art technology into the rehabilitation process can make a positive contribution.